Physiology - Urunova Mashhura Allamuradovna (Zien Journals, 2022)
The basic principles of physiology, which are supplemented by anatomy histology and medicine as a fan of physiology, are based on the human body's response to the environment of the living organism. teaches.
Keywords: Gistalogy; Cytology; Physiology; Anatomy